Speaking of Sex: Critical Reflections for Forensic Anthropologists - Taylor M. Flaherty; Liam J. Johnson; Katharine C. Woollen; Dayanira Lopez; Katherine Gaddis; SaMoura L. Horsley; Jennifer F. Byrnes (Humans, 2023)
Forensic anthropologists have a responsibility to appropriately relay information about a decedent in medicolegal reports and when communicating with the public. The terms ‘sex’ and ‘sex estimation’ have been applied with numerous, inconsistent definitions under the guise that sex—a broad, complex concept—can be reduced to a female/male binary. This binary does not reflect biocultural realities and harms those whose bodies do not meet social expectations of maleness or femaleness. The University of Nevada, Las Vegas’ Forensic Anthropology and Bioarchaeology Laboratory (UNLV FAB Lab) advocates for the use of the term ‘assigned sex at birth’ (ASAB) to highlight that binary sex is not biologically inherent to the body, but rather, assigned by society. Additionally, we call for the use of disclaimers in case reports to denote the limitations of ASAB estimation methods, the differentiation between those with mixed trait expression (i.e., indeterminate) and those on whom an ASAB analysis cannot be performed (i.e., unknown), and the included consideration of gender in forensic anthropology research and case reports. Such applications challenge biological normalcy, allowing forensic anthropologists to actively advocate for those whose bodies do not meet biocultural expectations.